2020
DOI: 10.3390/cells9030753
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Synergy of NKp46 and Co-Activating Signals in Various NK Cell Subpopulations: Paving the Way for More Successful NK-Cell-Based Immunotherapy

Abstract: The NK cell population is characterized by distinct NK cell subsets that respond differently to the various activating stimuli. For this reason, the determination of the optimal cytotoxic activation of the different NK cell subsets can be a crucial aspect to be exploited to counter cancer cells in oncologic patients. To evaluate how the triggering of different combination of activating receptors can affect the cytotoxic responses of different NK cell subsets, we developed a microbead-based degranulation assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 107 publications
(222 reference statements)
0
17
0
Order By: Relevance
“…The majority of human NK cells in the peripheral blood is the subset which is best characterized by diminished expression of CD56 and express high levels of CD16 ( Figure 1 ) ( 44 , 45 ). Several recent studies have suggested that unlike this traditional model, CD16 + CD56 dim and CD16 - CD56 bright NK cells may also originate from separate lineages ( 36 38 , 45 , 46 ).…”
Section: Natural Killer Maturation Phenotypes Distribution and Funcmentioning
confidence: 96%
See 1 more Smart Citation
“…The majority of human NK cells in the peripheral blood is the subset which is best characterized by diminished expression of CD56 and express high levels of CD16 ( Figure 1 ) ( 44 , 45 ). Several recent studies have suggested that unlike this traditional model, CD16 + CD56 dim and CD16 - CD56 bright NK cells may also originate from separate lineages ( 36 38 , 45 , 46 ).…”
Section: Natural Killer Maturation Phenotypes Distribution and Funcmentioning
confidence: 96%
“…Meanwhile, mature NK cells gain self-tolerance and effector-functions by loss of CD34 and ckit accompanied by sequential expression of CD56, CD94, and the killer C-type lectin receptor (CD161) (24,32,33). Mature NK cells can progress into 2 final developmental stages, with respect to the expression of CD56 and CD16 (34)(35)(36)(37)(38).…”
Section: Natural Killer Cell Development and Maturationmentioning
confidence: 99%
“…An alternative method to promote NK-cell expansion without feeder cells is monoclonal antibodies (mAb), such as the combination of anti-CD52 and anti-CD3, which demonstrated a favorable growth of NK-cells while suppressing CD4 + T-cells from peripheral blood mononuclear cell (PBMC) [ 57 ]. Moreover, activation using microbeads covered with antibodies against various NK receptors, such as NKp46, 2B4, DNAM-1, CD2, and CD18, is another strategy that can improve NK-cell expansion and activation [ 58 ].…”
Section: Nk Sources and Expansionmentioning
confidence: 99%
“…NKp46 acts as a coactivation receptor which triggers NK cell cytotoxicity by synergistic effects with other activating receptors. Researches confirmed that NKp46 could coengage with 2B4, CD2, NKG2D, and DNAM-1, transmitting activation signals to enhance the Ca 2+ flux of NK cells further [ 52 , 53 ]. However, we still do not know if synergistic signals of NKp46 and other coactivation receptors are the same as the synergistic signals of NKG2D and 2B4.…”
Section: Activating Receptorsmentioning
confidence: 99%